Om Grue-Sørensen og begrebet ’opdragende undervisning’ (Kant, Herbart) som almenpædagogisk kategori: – med henblik på spørgsmålet om aktuel relevans - Pio, Frederik (Studier i Pædagogisk Filosofi, 2018)
Grue-Sørensen’s concept of ’educational teaching’ is traced back to an original infl uence from Herbart and Kant. On this background the article attempts to interpret, how one can understand a concept of educationalteaching today. With that, the concept is shown to have its root in a tradition of general education and Grue-Sørensen is shown to be a Danish representative of this. However, in research programs as well as educational programs this tradition has generally been under increasing pressure the last approximately 30 years. Grue-Sørensen and his possible relevance today is discussed in connection with a potential revitalization of a general educational thinking in our current postmodern epoche of higher education.